Metabolic energy sensors as targets for designing host-directed therapies for tuberculosis - Cheng, Catherine Y. (2019)
A wealth of scientific and clinical evidence during the past few years has lent credence to the idea that key components of the host immune effector mechanisms can be targeted to boost current tuberculosis (TB) treatment and control patient relapse. These host‐directed strategies not only accelerate the clearance of pathogens but also have the ability to limit overt inflammation and pathology, which are associated with the tissue damage. Studies have indicated that inflammatory responses are intrinsically linked to cellular metabolism and together drive the fate of many host responses, coupling host survival with the capacity to respond to infectious insult. Metabolic sensors such as mammalian target of rapamycin, AMP‐activated protein kinase, and sirtuin 1 are central regulators of host metabolic alterations and play important roles in immune responses against infections. The present review discusses the functions of AMP‐activated protein kinase and sirtuin 1, with a focus on their role in immune homeostasis and how manipulating the AMP‐activated protein kinase–sirtuin 1 axis with drugs can modulate immunity to tuberculosis.